Positron emission tomography imaging of a novel Anxa1‐targeted peptide 18F‐Al‐NODA‐Bn‐p‐SCN‐GGGRDN‐IF7 in A431 cancer mouse models. (20th July 2020) - Chen, Fei; Xiao, Yichun; Shao, Kejing; Zhu, Bao; Jiang, Mengjun
Abstract : Annexin 1 (Anxa1) is a highly specific surface marker of tumor vasculature in the lung and prostate solid tumors. The IF7 peptide was modified with a hydrophilic linker, GGGRDN, and coupled with a new bifunctional chelating agent NODA‐Bn‐p‐SCN. The resulting peptides (NODA‐Bn‐p‐SCN‐GGGRDN‐IF7) were successfully labeled with Al 18 F. The targeting characteristics of the radiolabeled peptides were evaluated in the Anxa1 positive A431 tumor model. Micro‐positron emission tomography (micro‐PET) imaging revealed that the A431 tumors were clearly visualized (5.74 ± 1.13%ID/g, 3.92 ± 0.78%ID/g and 1.30 ± 0.43%ID/g at 0.5, 1, and 2 h post‐injection, respectively). Anxa1 binding specificity was also demonstrated by reduced tumor uptake after co‐injection with excessive unlabeled GGGRDN‐IF7 peptide at 30, 60, and 120 min post‐injection. 18 F‐Al‐NODA‐Bn‐p‐SCN‐GGGRDN‐IF7 might be a potential PET imaging agent for detecting Anxa1 levels in cancers due to the favorable characteristics such as convenient synthesis, specific Anxa1 targeting, and good tumor uptakes. Abstract : Anxa1 is a highly specific surface marker of tumor vasculature in the lung and prostate solid tumors. 18 F‐Al‐NODA‐Bn‐p‐SCN‐GGGRDN‐IF7 might be a potential PET imaging agent for detecting Anxa1 levels in cancers due to the favorable characteristics such as convenient synthesis, specific Anxa1 targeting, and good tumor uptakes.